Clinical success rate of fissure sealants: One-year follow-up - Figen Seymen; Pelin Barlak; Cengiz Aydınoğlu; Dilara Bektaş; Mine Koruyucu (Istanbul University, 2021)
Purpose: The aim of this study is to evaluate clinical success rate of resin-based fissure sealants applied at Istanbul University, Department of Pediatric Dentistry after 1 year of application. Materials and methods: Children with at least one pair of caries-free permanent first molars with deep pits and fissures were included in the study. The ages of children ranged from 7-13 (mean age:9.2±1.22). Resin-based fissure sealant was applied to the 322 fissures of the first permanent molars in 100 children. 12 months after the application, children were recalled for examination. Recall examinations were carried out by the same dentist. Fissure sealants were evaluated at 12th month by using Ryge criteria: Retention (R), precence of caries (PC), marginal adaptation (MA), marginal discoloration (MD) and cracking (C). Results: 12 months after the application, all of the children were recalled and fissure sealants were examinated. Our findigs are: R: Alpha 95 (29.5%), Bravo: 143 (44.4%), Charlie: 84 (26%); PC: Alpha 274, Bravo 48 (14.9%); MD: Alpha 322; MA: Alpha 279, Bravo 43 (13.3%); C: Alpha 321, Bravo 1 (0.3%). Conclusion: The preventive effects of the sealant are only maintained as long as it remains completely intact and bonded in place. After applying fissure sealants, patients must be recalled and sealants must be checked to provide retention and marginal adaptation.